Prevalence and genotype distribution of HPV infection among women in Xiamen, China - Shen, Ye; Huang, Yanru; Wang, Wenbo; Zhang, Jian; Chen, Xiaolu; Zhang, Lutan; Huang, Xiaomei; Ge, Yunsheng (Frontiers in Microbiology, 2023)
Abstract Objective: Cervical cancer is strongly associated with human papillomavirus (HPV) infection, and the genotype distribution of HPV varies across geographic regions. This study aimed to evaluate the prevalence of HPV and genotype distribution among female populations in Xiamen, Fujian Province, China, which can be conducive for local governments to formulate cervical cancer screening and HPV vaccine strategies. Methods: Clinical specimens were collected from 47,926 participants aged 16-92 years at the Women and Children’s Hospital, Xiamen University, from November 2019 to June 2020. HPV DNA was extracted and detected using conventional PCR, followed by HPV subtype-specific hybridisation. HPV infection rates based on different groups were compared using the 2 test. HPV prevalence and the corresponding 95% confidence intervals (95% CI) were calculated using SPSS 19.0. Results: The overall HPV prevalence among the 47,926 cervical swabs that were analysed was 15.13%, of which single, double, and multiple infections accounted for 12.07%, 2.25% and 0.81%, respectively. The age-specific prevalence of HPV infection presented a “U” curve with a HPV prevalence peak observed in women aged <20 years. The gynaecology clinic group had significantly higher HPV positive rates than the health examination group (P<0.001). The five most common HR-HPV subtypes in Xiamen were HPV52, 58, 16, 51, and 39 (2.69%, 1.63%, 1.23%, 1.05%, and 0.98%, respectively). The five most common LR-HPV subtypes were HPV54, 61, 81, 70, 34, and 84 (0.92%, 0.86%, 0.71%, 0.45% and 0.35%, respectively).Conclusion: This study analysed the current HPV prevalence and genotype distribution among women in Xiamen. Our findings demonstrate that the 9-valent HPV vaccine is recommended for regular immunisation in Xiamen. It is necessary for elderly women to participate in HPV screening to decrease the morbidity and mortality of cervical cancer. Keywords: Human papillomavirus, Prevalence, Genotype, Cervical cancer, Infection